Biscuit Formulation With Substitution Of Mackerel Fish Meal (Rastrelliger Sp.) And Black Rice Flour (Oryza Sativa L. Indica) As An Alternative Snack For Diabetes Mellitus Sufferers - Rizka Adelia Lubis; Syahrial Syahrial; Deni Elnovriza (Majalah Kedokteran Andalas, 2024)
Objective: This research aims to develop a biscuit formulation with the substitution of mackerel fish flour and black rice flour as an alternative snack for diabetes mellitus sufferers.Method: This research was an experiment with a Completely Randomized Design (CRD) consisting of four treatments, namely 0% (F0), 25% (F1), 50% (F2), and 75% (F3). Organoleptic tests were carried out on 7 trained panelists. The organoleptic test data was tested for normality using the Shapiro Wilk test. The results of the data distribution are normally distributed, so to determine whether there are real differences in each treatment, the data is processed using the ANOVA test at the 5% level, if it is known that there are significant differences (p value <0.05), followed by the Duncan New Multiple Range Test (DNMRT) at the 5% level to see which treatments are different. Results: The biscuits selected based on organoleptic tests were F1 biscuits with a water content of 3.1%, ash 1.5%, protein 5.2%, fat 3%, magnesium 117 gr, anthocyanin 14.88 mg. Conclusion: Biscuits substituted for mackerel fish flour and black rice flour can be used as an alternative snack for diabetes mellitus sufferers.Keywords: diabetes mellitus, biscuits, mackerel flour, black rice flour